2014
DOI: 10.1177/1941874414533351
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis

Abstract: Neurocysticercosis, the most common helminthic infection of the nervous system, is a major cause of acquired epilepsy worldwide. The disease occurs when humans become intermediate hosts of the tapeworm Taenia solium after ingesting its eggs by contagion from an asymptomatic Taenia carrier. Within the nervous system, parasites may locate in brain parenchyma, subarachnoid space, ventricular system, or spinal cord, causing several pathological changes that are responsible for the clinical pleomorphism of the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 59 publications
0
37
0
10
Order By: Relevance
“…Seizures are the most common clinical manifestation, while headache and focal neurological deficits may occur in 20-40% of affected patients [6]. Confusion, ataxia, and psychosis are seen in fewer than 10% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are the most common clinical manifestation, while headache and focal neurological deficits may occur in 20-40% of affected patients [6]. Confusion, ataxia, and psychosis are seen in fewer than 10% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal cycle of transmission, the adult T. solium inhabits the small intestine of humans, and gravid proglottids are detached from the distal end of the worm and are passed with the feces to the environment (2). When pigs feed on human feces containing T. solium eggs, the eggs subsequently lose their coats and liberate oncospheres, which are infective to humans (2). Thus, humans who eat improperly cooked infected pork meat may themselves become infected (2).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are the only definitive hosts for the adult tapeworm, whereas both pigs and humans may act as intermediate hosts for the larval form, called cysticercus (2). In the normal cycle of transmission, the adult T. solium inhabits the small intestine of humans, and gravid proglottids are detached from the distal end of the worm and are passed with the feces to the environment (2). When pigs feed on human feces containing T. solium eggs, the eggs subsequently lose their coats and liberate oncospheres, which are infective to humans (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a common infection of the nervous system and is known to be the primary cause of preventable epilepsy in many developing countries [2][3][4] . Epidemiologic studies have demonstrated tight clustering household or household contacts with NCC patients have three times higher risk having positive serology for cysticercosis compared with controls 5 .…”
Section: Introductionmentioning
confidence: 99%